Repair of bone defects using dynamic fabricated tissue-engineered bone based on a bio-derived porous bone scaffold. Issue 5 (2nd September 2016) - Song, Kedong; Li, Liying; Ji, Lili; Li, Siyuan; Mu, Chunfeng; Wang, Yiwei; Liu, Tianqing
ABSTRACT: Fabrication and transplantation of tissue-engineered bones in a rotating wall vessel bioreactor (RWVB) was studied in the present study aiming to repair segmental bone defects. Osteoblasts were transfected with green fluorescent protein prior to seeding on bio-derived porous bone scaffolds at a density of 1 × 10 6  cells/mL and cultured in an RWVB for one week. For comparison, constructs were also cultured in a static condition. Morphology and structure of fabricated bones were examined using an inverted microscope, scanning electron microscope and histology analysis via hematoxylin–eosin and toluidine blue staining. Moreover, an animal model for repairing segmental bone defects of a Zelanian rabbit was used to assess the efficacy and biosafety of fabricated bones. In conclusion, tissue-engineered bones grew favorably in RWVB. In animal study, a preliminary repair of bone defects was noticed only in the experimental group after 4 weeks of implantation. Using RWVB, the fabricated tissue-engineered bone constructs were approved with better bio-capability in repairing the segmental bone defect.